Angela: portrait of a revolutionary - Professor (London: Shere Books Limited, 1972)
In 1970 black militants attempted to kidnap a judge and four other hostages to force the American authorities into releasing the famous Soledad Brothers. The attempt ended in a bloody shooting and the kidnappers were arrested. Angela Davis was charged with obtaining the guns used and consequently imprisoned as an accomplice. Angela's arrest and trial raised a storm of protest that threatened to explode into fierce rebellion.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Davis, Angela Y. -- 1944-; Women revolutionaries -- United States -- Biography; Human rights -- Political aspects; African Americans -- Race relations; African American women -- Biography